MODELING THE ALLOCATION OF HAZARDOUS SUBSTANCES INTO THE AIR OF WORKING AREA STATIONS RUN THE MACHINE-BUILDING PLANTS - L.N. ALEKSEENKO (Advanced Engineering Research)
We obtain polynomial dependence, which can be used for theoretical calculation of the most likely content of harmful substances in exhaust gases at various operating modes of the machines when they were run and tested and, subsequently, to predict the quality of air in industrial premises obkatochnyh sites that will help to develop the requirements for automated alarm systems on chemical hazards, as well as to optimize the positions of energy modes of ventilation.